LDHA: The Obstacle to T cell responses against tumor - Tang, Yu; Gu, Shuangshuang; Zhu, Liqun; Wu, Yujiao; Zhang, Wei; Zhao, Chuanxiang (Frontiers in Oncology, 2022)
Immunotherapy has become a successful therapeutic strategy in certain solid tumors and hematological malignancies. However, this efficacy of immunotherapy is impeded by the limited success rates. Cellular metabolic reprogramming determines the functionality and viability in both cancer cells and immune cells. Extensive research has unraveled that the limited success of immunotherapy is related to immune evasive metabolic reprogramming in tumor cells and immune cells. As an enzyme that catalyzes the final step of glycolysis, LDHA has become a major focus of research. Here, we have addressed the structure, localization and the biological features of LDHA. Further, we have discussed the various aspects of epigenetic regulation of LDHA expression, such as histone modification, DNA methylation, m6A RNA methylation and transcriptional control by noncoding RNA. With focus on extrinsic (tumor cells) and intrinsic (T cells) functions of LDHA on T cell responses against tumor, in this article we have reviewed the current status of LDHA inhibitors, and their combination with T cell-mediated immunotherapies and postulated different strategies for future therapeutic regimens.